An Iterated Function System for A-contraction mapping - et. al., Priyanka, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Fractals play main role in dynamical systems, quantum mechanics, biology, computer graphics, geophysics, astrophysics and astronomy etc. The Iterated Function Systems (IFS) is an emerging scheme provides an important implement to mathematicians for manipulation and description of the attractors applying common mathematical algorithms. The intension of the present study is to originate the novel IFS expressly “A-Iterated Function System” either “AIFS” defined on a complete metric space using a unique class of contraction maps known as A-contractions; that was studied by various mathematicians. This study proves the uniqueness and existence of the attractor for AIFS. The analysis also establishes the Collage theorem for AIFS. To obtain our outcomes we utilizing some basic ideas and speculations given in the literature. Our outcomes extend, unify and generalize numerous consequences present in the literature.